Integrating MAPLETM in the teaching and learning of mathematics for business and economics - Md Ariffin, Latifah (2006)
MAPLETM technology has been trusted as an advanced mathematical and technical tool for over 25 years. In that time, millions of users all around the world have used and relied on the power of MAPLP" for their research, testing, analysis, design, teaching and schoolwork. MAPLpM is seen as easy to be incorporated into any undergraduate mathematical course. In this study, MAPLpM based materials were introduced into MTH 3004 (Applied Mathematics for Business and Economics) classrooms. Before the MAPLE'"M based material was developed, the analysis of student achievement during tests and final examination was done based on the previolls semester's performances. This analyses was conducted to identify the difficult topics that student's could not understand the most. Based on the analyses, non-linear inequalities, inverse of three by three matrix, integrations, limits and set operation are the topics that report a high number of failures in all the examinations. The analysis was done with manual calculation and the graph was plotted using Microsoft EXCEL. Some MAPLpM based materials had been used in tutorial classes and had demonstrated MAPLpM as problem III solver. Positives feedback was then received from the student's since they claim that they could understand the particular topics clearly and could answer most of the questions given in quizzes and tutorials very well. However, there are still weaknesses in this MAPLpM based materials that had been identified during the demonstration which can be improved. Some students suggested revising the MAPLpM -based materials in the technical aspects. These aspects include the type of font, color of text and the size of worksheet. Thus, the efforts to integrate MAPLpM into teaching and learning MTH 3004 environment are hope to increase the understanding levels amongst student's and to increase their achievements in all assessments throughout the semester. However, it is to be emphasized that MAPLETM was not to replace the teacher's role in the classroom but to help them to become more efficient and effective in their teaching.